Accelerometers in Monitoring Systems for Rail Vehicle Applications: A Literature Review - Emil Tudor; Ionuț Vasile; Daniel Lipcinski; Constantin Dumitru; Nicolae Tănase; Florian Drăghici; Gabriel Popa (Applied System Innovation, 2025)
This document comprehensively analyses the literature on accelerometers used in monitoring systems designed for rail vehicle applications. It reviews the current research on this topic and highlights key findings, methodologies, and trends in the field. Additionally, it discusses the role of accelerometers in enhancing safety and performance within rail vehicle systems. This review is structured into several sections: Introduction, Fundamentals of Accelerometer Data, Signal-Processing Techniques, Examples of Accelerometers Used in Railway Monitoring Systems, and a Guide for Choosing the Right Accelerometer. One of the primary contributions of this paper is recommending the best accelerometer in terms of cost and performance for use in the rail vehicle industry. Future work will consider using an online detection tool for the acceleration of the frame of the railway coach and signalization of the peak values using the train intercom to the driver and static diagnosis systems. This approach aims to facilitate the detection of track irregularities, wind influence, and failures of the coach suspensions, which can be easily detected.